Molecular techniques used for study of soil bacterial diversity - Singh A.K.; Singh V.; Chaturvedi V.K.; Singh M.P.; Verma V. (My University, 2025)
Stability of any ecosystem depends on the presence of microbial diversity of that ecosystem. The culturing of bacteria in laboratories is a difficult task due to unidentified nutritional requirement and optimum growth temperature for different bacteria. These two factors are limiting steps for study of bacterial diversity in soil using conventional methods. The already described bacterial diversity represents a total of 5,000 bacterial species which is a minor fraction (<3%) of estimated bacterial species. The cultivable and non-cultivable bacterial species are being identified by use of traditional cultivable and 16S rRNA metagenomic strategies respectively. The advance molecular techniques such as amplified ribosomal DNA restriction analysis (ARDRA), terminal restriction fragment length polymorphism (T-RFLP), denaturing gradient gel electrophoresis (DGGE) or temperature gradient gel electrophoresis (TGGE) and metagenome of 16S rRNA gene have potential to explore and established bacterial diversity in soil. In this chapter attempts have been made to highlight different molecular techniques for studies of bacterial diversity in soil. © 2017 Nova Science Publishers, Inc.